Molecular characterization of HIV-1 near-full-length proviral quasispecies in monocytes from patients across different virological responses - Li, Jian; Zhang, Chuyu; Zou, Zhenyi; Liang, Yawen; Ma, Peng; Lan, Yun; Li, Quanmin; Kong, Qian; He, Ruiying; Li, Linghua; Chen, Weilie (Frontiers in Microbiology, 2025)
IntroductionLow-level viremia (LLV) in HIV infection, defined as detectable but low plasma viral load, is associated with an increased risk of virological failure (VF); however, the mechanisms underlying LLV remain unclear. Monocytes, as potential viral reservoirs, can migrate into tissues and differentiate into tissue-resident macrophage reservoirs, playing a critical role in viral dissemination and potentially driving persistent viremia.MethodsThis study aimed to analyze and compare the molecular characteristics of near-full-length HIV-1 proviral DNA quasispecies from monocytes in three distinct virological response groups: VF, LLV, and virological suppression (VS). Genetic diversity, drug resistance mutations (DRMs), and viral tropism were assessed.ResultsOf the 198 single quasispecies sequences obtained from 54 patients, 177 were identified as near-full-length genomes (NFLGs; length >8.6 kb, without inversion). The VF group demonstrated a higher prevalence of intact proviruses (82.6%) compared to the LLV (50.0%) and VS groups (22.2%). Compared to the VF group, the LLV group exhibited significantly higher hypermutation rates (42.35% vs 8.78%, p < 0.01) and greater median genetic distance (0.0446 vs 0.0186, p < 0.01). Moreover, monocytes harbored proviral DNA with DRMs that were divergent from those detected in plasma RNA. No significant differences in viral tropism were observed across groups.DiscussionNear-full-length proviral quasispecies amplified from monocytes demonstrated distinct characteristics across virological response groups. Notably, proviral quasispecies in the LLV group exhibited higher genetic diversity, suggesting unique evolutionary dynamics under low-level viral replication. These findings underscore the importance of investigating proviral quasispecies within monocytes to better understand their role in persistent HIV viremia.